Hacker, Fear, and Harm: Data Breaches and National Security - Sukmawan, Denny Indra; Setyawan, David Putra (Global Strategis, 2023)
This research explains data breaches as national security threat by using cyber security dilemma and cyber harm approaches. For long, Indonesia adopted comprehensive national security system that covers state defense, state security, public security and human security. Cyber security dilemma explains data breaches as threats to state defense and security dimensions. While cyber harm explains it as threats to public and human security dimensions. Furthermore, we found that: (1) non-state actors have influence to escalate cyber security dilemma in long term; (2) the state response by increasing defense and security sector's budget; and (3) the threats of data breaches to public and human security took place when government and corporations neglect the responsibilities to protect data and privacy of citizen and consument, as well as non-state actors conduct cyber attacks intentionally. The methodology is descriptive -qualitative and quantitative. While the data covered data breaches incidents in Indonesia during August-September 2022, literatures such as books, journal articles and online articles is also used. Keywords: cyber security, cyber space, cyber threats, cyber security dilemma, cyber harm,  data breaches, bjorka, national security   Penelitian ini menjelaskan pelanggaran data sebagai ancaman keamanan nasional dengan menggunakan pendekatan dilema keamanan siber dan bahaya siber. Indonesia mengadopsi sistem keamanan nasional yang komprehensif dan melingkupi dimensi pertahanan negara, keamanan negara, keamanan publik dan keamanan insani sejak lama.  Dilema keamanan siber menjelaskan pelanggaran data sebagai ancaman ke dimensi pertahanan negara dan keamanan negara. Sementara bahaya siber menjelaskan ancaman ke dimensi keamanan publik dan keamanan insani. Kami menemukan: (1) aktor-aktor non-negara mampu mengeskalasi kondisi dilema keamanan siber dalam waktu lama; (2) respons negara dengan meningkatkan anggaran bagi instansi-instansi sektor pertahanan dan keamanan siber; dan (3) ancaman pelanggaran data terhadap keamanan publik dan keamanan insani justru terjadi ketika pemerintah dan perusahaan lalai atas tanggung jawab untuk melindungi data dan privasi warga negara dan pelanggan mereka, termasuk ketika aktor-aktor non-negara melakukan serangan siber dengan sengaja. Metodologi penelitian ini deskriptif -kualitatif dan kuantitatif. Data digunakan mencakup insiden siber yang terjadi di Indonesia selama Agustus-September 2022, literatur-literatur seperti buku, artikel jurnal dan artikel daring. Kata-kata kunci: keamanan siber, ruang siber, ancaman siber, dilema keamanan siber, bahaya siber, pelanggaran data, bjorka, keamanan nasional